The Motivational Underpinnings of Intentions to Use Doping in Sport: A Sample of Young Non-Professional Athletes - Chirico, Andrea; Lucidi, Fabio; Pica, Gennaro; Di Santo, Daniela; Galli, Federica; Alivernini, Fabio; Mallia, Luca; Zelli, Arnaldo; Kruglanski, Arie W.; Pierro, Antonio (International Journal of Environmental Research and Public Health, 2021)
Doping use is considered as a deviant behavior in sport contexts, and it is necessary to recognize preventive factors to shut down the negative consequences. We proposed that athletes experiencing loss of personal significance would be more prone to doping use intentions. This pathway should occur through the effect of the enhanced predominance of obsessive (vs. harmonious) passion that such athletes experience concerning their sport activity, which, in turn, facilitates the adoption of moral disengagement strategies to find justifications for it, when they perceive that significant others approve their intention. The study relied on a cross-over design, with a convenience sample of 437 athletes recruited at four sports sciences Universities evenly distributed in Italy. Questionnaires administered contained a validated tool based on Kruglanski’s theorizing on radical and deviant behavior (e.g., Loss of Significance, Obsessive, and Harmonious passion) and deriving from social cognitive theory (e.g., Moral disengagement). Results of the study tested a serial mediation moderated model, which links the different variables to explain the influence they have on the intentions to use doping. Overall, this research suggests a motivational dynamic that may be at the heart of illicit behaviors in sport, such as using drugs-enhancing performance potentially among athletes of all kinds.